Evaluation of the cognitive function of a hospitalized elderly population - Lino, Ireneia (2009)
Objectives: Evaluation of level of consciousness and cognitive function in an elderly population admitted in an internal medicine department. Methods: One hundred and fifty patients older than 65 years were studied, 88 males and 62 females, using the Mini-Mental State Examination.Results: The number of male patients was higher than female patients (57.5% vs 42.5%). We found an elevated average age with 56.6% of patients in the 8th decade of life and 23.3% of patients older than 80 years. Sixty one percent of patients were illiterate. We detected a low or very low score correlated with the presence of dementia in 44% of patients included in this study. This incidence was higher in female (51.6%) than male patients (40.9%).Conclusions: This study shows that most patients admitted in an internal medicine department are illiterate, elderly, with loss of cognitive function and completely dependent. Dementia is a serious problem of public health and economic issues of modern societies.